ASSERTIVE ILLOCUTIONARY SPEECH ACTS OF THE NORMALIZATION OF SAUDI ARABIA-ISRAEL RELATIONS ON CNN ARABIC NEWS - Humaira Izzahurrohman; Nani Darmayanti; Fahmy Lukman (UIN Raden Mas Said Surakarta, 2025)
This study examines how assertive illocutionary speech acts are employed in CNN Arabic media discourse to convey ideology and power dynamics in news coverage of the normalization of Saudi Arabia-Israel relations. This study employed descriptive-qualitative method with a critical pragmatics approach using Korta and Perry (2011) model which includes stances, critique, and reproduction. The data in the forms of texts were collected by documentation from six CNN Arabic news segments featuring statements by prominent figures, including Benjamin Netanyahu, Anthony Blinken, and Faisal bin Farhan. The data were analyzed by interpretation with the result that CNN Arabic tends to prioritize representing social actors from the Unites States and Israel as its main sources of information that from Saudi Arabia and Palestine. Through assertive speech acts, such stating, explaining, telling, and claiming, the media constructs discourses that favor the Western pro-normalization hegemonic ideology. This study reveals that these language strategies are not neutral but play a role in reproducing power and framing public opinion on sensitive geopolitical issues in the Middle East.